GIFTED CHILD AS A PERSONALITY WITH SGIFTED CHILD AS A PERSONALITY WITH SPECIAL NEEDS IN THE INCLUSIVE ENVIRONMENT OF THE EDUCATIONAL ESTABLISHMENT - Demchenko, Olena; Zaitseva, Olga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The article deals with the contradiction between the recognition of gifted children in the theoretical discourse as a category of persons with special educational needs, on the one hand, and the low level of their involvement in the inclusive educational environment at school practice, on the other. The necessity of providing talented individuals the status of an important group of atypical children, whose capabilities disclosing is complicated by the disharmonious type of mental development, high level of claims, a number of social and psychological problems is grounded. The needs and problems of gifted children and the system of social and pedagogical work, aimed forming their subjectivity in terms of inclusive education are defined.